Larval fish dynamics in the shallow nearshore of Eastern Algoa Bay with particular emphasis on the effects of currents and swimming abilities on dispersal - Pattrick, Paula (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2008)
The larval fish assemblage in the shallow, nearshore region of a proposed marine protected area (MPA) in eastern Algoa Bay, temperate South Africa was investigated. Current velocities and direction and the swimming abilities of late-stage larvae were further assessed to determine potential larval movement to and from the MPA. In total, 6045 larval fishes were collected along two depth contours (~5m and ~15m) in the shallow nearshore of eastern Algoa Bay using stepped-oblique bongo net tows, twice per season for two years (March 2005 "“ January 2007). These larvae represented 32 families and 78 species. The Gobiidae, Cynoglossidae, Clupeidae, Engraulidae and Sparidae were the dominant fish families. Catches varied significantly between seasons peaking in spring with a mean of 64 larvae/100m3. Preflexion stage larvae dominated catches (75%). All developmental stages of Diplodus capensis, Engraulis capensis, Heteromycteris capensis, Sardinops sagax and Pomadasys species were found in the study area. It appears that these species use the shallow nearshore as a nursery area. Analysis of 12 months (May 2006 "“ May 2007) data from a bottom-moored Acoustic Doppler Current Profiler within the study area showed that offshore south eastward (39%) and onshore north westward currents (33%) dominated. The south westward current (15%) and north eastward current (12%) occurred less frequently. Current velocity decreased with depth in the nearshore, with a mean velocity of ~29 cmsâ »Â¹ recorded at a depth of 4 m and a mean velocity of ~11 cmsâ »Â¹ recorded at a depth of 14 m. Understanding the dispersal and movement of marine fish larvae in coastal habitats requires knowledge of active swimming abilities. The critical speed and endurance swimming of late stage larvae of two common inshore species occurring in the study area, Diplodus capensis and Sarpa salpa (Family Sparidae), were measured in a laboratory swimming chamber. The mean U-crit value for D. capensis (18.6 cmsâ »Â¹) was similar to that of S. salpa (18.0 cmsâ »Â¹), whereas mean endurance (km swum) was greater in S. salpa (8.4 km) than D. capensis (5.9 km). These swimming abilities exceed the average current velocities observed in the shallow nearshore providing larvae with the ability to greatly alter their passive dispersal trajectories and ultimately influence their distribution in the nearshore.
Keywords: Fishes -- Larvae -- Eastern Cape -- Algoa Bay; Marine parks and reserves -- Eastern Cape -- Algoa Bay; Fishes -- Larvae -- Ecology -- Eastern Cape -- Algoa Bay; Fishes -- Larvae -- Dispersal -- Eastern Cape -- Algoa Bay; Fishes -- Development -- Eastern Cape -- Algoa Bay